Profilin 1 Induces Tumor Metastasis by Promoting Microvesicle Secretion Through the ROCK 1/p-MLC Pathway in Non-Small Cell Lung Cancer - Wang, Ya; Lu, Yichen; Wan, Rongjun; Wang, Yang; Zhang, Chunfang; Li, Min; Deng, Pengbo; Cao, Liming; Hu, Chengping (Frontiers in Pharmacology, 2022)
Profilin 1 (PFN1), an actin-binding protein, plays contrasting roles in the metastasis of several cancers; however, its role in non-small cell lung cancer (NSCLC) metastasis remains unclear. Here, PFN1 expression was upregulated in metastatic NSCLC tissues. PFN1 overexpression significantly promotes NSCLC metastasis in vitro and in vivo. Proteomics analysis revealed PFN1 involvment in microvesicles (MVs) secretion. In vitro experiments confirmed that PFN1 overexpression increased secretion of MVs. MVs are important mediators of metastasis. Here, we show an increased abundance of MVs in the sera of patients with metastatic NSCLC compared to that in the sera of patients with non-metastatic NSCLC. Both in vitro and in vivo experiments revealed that PFN1 could increase MV secretion, and MVs derived from PFN1-overexpressing cells markedly promoted NSCLC metastasis. We then elucidated the mechanisms underlying PFN1-mediated regulation of MVs and found that PFN1 could interact with ROCK1 and enhance its kinase activity to promote myosin light chain (MLC) phosphorylation for MV secretion. Inhibition of ROCK1 decreased MV secretion and partially reversed the PFN1-induced promotion of NSCLC metastasis. Collectively, these findings show that PFN1 regulates MV secretion to promote NSCLC metastasis. PFN1 and MVs represent potential predictors or therapeutic targets for NSCLC metastasis.